Nationwide cloud-based integrated database of idiopathic interstitial pneumonias for multidisciplinary discussion. Issue 5 (18th May 2019) - Fujisawa, Tomoyuki; Mori, Kazutaka; Mikamo, Masashi; Ohno, Takashi; Kataoka, Kensuke; Sugimoto, Chikatoshi; Kitamura, Hideya; Enomoto, Noriyuki; Egashira, Ryoko; Sumikawa, Hiromitsu; Iwasawa, Tae; Matsushita, Shoichiro; et al.
Multidisciplinary discussion (MDD) requiring close communication between specialists (clinicians, radiologists and pathologists) is the gold standard for the diagnosis of idiopathic interstitial pneumonias (IIPs). However, MDD by specialists is not always feasible because they are often separated by time and location. An online database would facilitate data sharing and MDD. Our aims were to develop a nationwide cloud-based integrated database containing clinical, radiological and pathological data of patients with IIPs along with a web-based MDD system, and to validate the diagnostic utility of web-based MDD in IIPs. Clinical data, high-resolution computed tomography images and lung biopsy slides from patients with IIPs were digitised and uploaded to separate servers to develop a cloud-based integrated database. Web-based MDD was performed using the database and video-conferencing to reach a diagnosis. Clinical, radiological and pathological data of 524 patients in 39 institutions were collected, uploaded and incorporated into the cloud-based integrated database. Subsequently, web-based MDDs with a pulmonologist, radiologist and pathologist using the database and video-conferencing were successfully performed for the 465 cases with adequate data. Overall, the web-based MDD changed the institutional diagnosis in 219 cases (47%). Notably, the MDD diagnosis yielded better prognostic separation among the IIPs than did the institutional diagnosis. This is the first study of developing a nationwide cloud-based integrated database containing clinical, radiological and pathological data for web-based MDD in patients with IIPs. The database and the web-based MDD system that we built made MDD more feasible in practice, potentially increasing accurate diagnosis of IIPs. A cloud-based integrated database of idiopathic interstitial pneumonias containing clinical, radiological and pathological data along with a web-based multidisciplinary discussion system can make discussions more feasible and improve disease management http://ow.ly/NqqD30nYenb